Wildfire effects on the hydrogeochemistry of a river severely polluted by acid mine drainage. (15th April 2023) - Romero-Matos, Jonatan; Cánovas, Carlos R.; Macías, Francisco; Pérez-López, Rafael; León, Rafael; Millán-Becerro, Ricardo; Nieto, Jose Miguel
Highlights: First research evaluating the wildfire effects in a deeply AMD-polluted watershed. Temporal evolution of the hydrochemistry during the first rainfalls is shown. Rupture of previously documented common seasonal variations of an AMD-polluted river. Washout of wildfire alkaline ashes promotes natural attenuation of the river acidity. Hydrochemical tracers elucidate the wildfire influence on the water chemistry. Abstract: This study evaluates for the first time the impact of a large wildfire on the hydrogeochemistry of a deeply AMD-affected river at the beginning of the wet season. To accomplish this, a high-resolution water monitoring campaign was performed within the basin coinciding with the first rainfalls after summer. Unlike similar events recorded in AMD-affected areas, where dramatic increases in most dissolved element concentrations, and decreases in pH values are observed as a result of evaporitic salts flushing and the transport of sulfide oxidation products from mine sites, a slight increase in pH values (from 2.32 to 2.88) and decrease in element concentrations (e.g.; Fe: 443 to 205 mg/L; Al: 1805 to 1059 mg/L; sulfate: 22.8 to 13.3 g/L) was observed with the first rainfalls after the fire. The washout of wildfire-ash deposited in the riverbanks and the drainage area, constituted by alkaline mineral phases, seems to have counterbalanced the usual behavior and patterns of the river hydrogeochemistry during autumn. Geochemical results indicate that a preferential dissolution occurs during ash washout (K > Ca > Na), with a quick release of K followed by an intense dissolution of Ca and Na. On the other hand, in unburnt zones parameters and concentrations vary to a lesser extent than burnt areas, being the washout of evaporitic salts the dominant process. With subsequent rainfalls ash plays a minor role on the river hydrochemistry. Elemental ratios (Fe/SO4 and Ca/Mg) and geochemical tracers in both ash (K, Ca and Na) and AMD (S) were used to prove the importance of ash washout as the dominant geochemical process during the study period. Geochemical and mineralogical evidences point to intense schwertmannite precipitation as the main driver of reduction in metal pollution. The results of this study shed light on the response of AMD-polluted rivers to certain climate change effects, since climate models predict an increase in the number and intensity of wildfires and torrential rain events, especially in Mediterranean climates. Graphical abstract: Image, graphical abstract